The use of possessive constructions in English and Slovene and the reference-point function of prenominal possessors - Lipovšek, Frančiška (Acta neophilologica, 2002)
The paper presents the findings of the study concerning the use of prenominal and postnominal constructions in English and Slovene. The study has been based on the cognitive approach according to which the possesor functions as a reference point facilitating identification of the possessee. The term "identification value" has been used in the study to refer to the cluster of properties that render a nominal compatible with the reference-point function. The main factors contributing to the identification value of the possessor nominal are its "topicality" (i.e. mental accessibility) and its "informativity" (i.e. ability to be an effective cue fot the identification of the relation between the possessor and the possessee). The findings of the study confirm that in both languages (i) the pronominal possessor has the reference-point function by default, and that (ii) the identification value of the possessor is the main factor determining the choice between the prenominal and the postnominal constructions.
Keywords: angleščina; besedne zveze; English; primerjalno jezikoslovje; Slovene; slovenščina